(untitled) (Research, Society and Development, 2021)
The research aimed to evaluate the physicochemical quality, and labeling of products used as hair straighteners. The parameters used were measurements of pH, viscosity, organoleptic characteristics, centrifugation, spreadability and prohibitive substance search. All tests were performed based on the Quality Control Guide for Cosmetic Products, published by the National Health Surveillance Agency (ANVISA). Ten samples of straighteners were evaluated, which were identified by letters in order to maintain confidentiality. The research method was experimental type with quantitative approach. Data analysis showed that the 10 samples had a pH value outside the specifications (5.0 to 7.0). Regarding the viscosity of the straighteners, it was possible to observe that the sample with the highest viscosity was the product sample A5 (6486 cP) whereas the sample with the lowest viscosity was sample A8 (801 cP). In the search for prohibitive substances, all samples were positive in the test for detecting formaldehyde with presence above 0,01% of formalin. Therefore, a stricter control for hair straighteners is necessary in view of the inadequacy of some evaluated parameters.